Adjuvant immunotherapy with autologous dendritic cells for hepatocellular carcinoma, randomized phase II study - Lee, Jeong-Hoon (Oncoimmunology, 2017)
Our previous phase I/IIA study showed that autologous dendritic cells (DCs) pulsed with tumor-associated antigens are well tolerated in patients with hepatocellular carcinoma (HCC). In this randomized, multicenter, open-label, phase II trial, we investigated the efficacy and safety of this DC-based adjuvant immunotherapy with 156 patients, who treated for HCC with no evidence of residual tumor after standard treatment modalities. Patients were randomly assigned to immunotherapy (n = 77; injection of 3 × 10(7) DC cells, six times over 14 weeks) or control (n = 79; no treatment). The primary end point was recurrence-free survival (RFS), and the secondary endpoints were immune response and safety. The RFS between the immunotherapy and control groups was not significantly different (hazard ratio [HR], 0.97; 95% confidence interval [CI], 0.60–1.56; p = 0.90). However, post-hoc subgroup analyses revealed that DC immunotherapy significantly reduced the risk of tumor recurrence of non-radiofrequency ablation (non-RFA) group patients (n = 83, HR, 0.49; 95% CI, 0.26–0.94; p = 0.03), whereas unexpectedly increased the risk of recurrence in RFA group (n = 61, p = 0.01). Tumor-specific immune responses were significantly enhanced (both p < 0.01) in the immunotherapy group. Baseline serum interleukin (IL)-15 was statistically correlated with RFS prolongation (HR, 0.16; 95% CI, 0.03–1.58; p = 0.001) within the immunotherapy groups. Overall adverse events were more frequent in the immunotherapy group (p < 0.001) but were mainly mild to moderate in severity. In conclusion, adjuvant immunotherapy with DC vaccine reduces the risk of tumor recurrence in HCC patients who underwent standard treatment modalities other than RFA. Baseline IL-15 might be a candidate biomarker for DC-based HCC immunotherapy.